Kontaktsoner og grenseområder: Interaksjon, konflikt og samarbeid i Norden, Midtøsten og Midtvesten ca. 1520–2020 - Kaveh, Chalak; Endre Tafjord, Harald; Teige, Ola; Grohse, Ian Peter; Holmberg, Susann; Hasle Joranger, Terje Mikael; Krøvel, Harald J; Okkenhaug, Inger Marie; Peksevgen, M. Şefik; Svendsen, Åsmund (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
This anthology takes up the subject of border areas and contact zones, both as actual places and as analytical concepts for understanding the past. What happens when different cultures, states and people meet, and what happens in and to the places and spaces where such meetings occur? These are among the questions that are elucidated in nine investigations that deal with several different examples from history, from the very concrete to the more metaphorical, and spanning macro to micro scales of study. The nine contributions range, in terms of time, from the transition from the Middle Ages to the early modern age at the beginning of the 16th century, up to our own era. Geographically, the investigations concentrate on three areas. One is the Nordic region: geographical and cultural contact zones are examined within and between the different Nordic countries. Several contributions deal with the period when Norway was part of a larger northern European composite state, Denmark-Norway. The second area is the Middle East. Here, both the royal court as a contact zone in the Ottoman Empire is discussed, as well as contact and conflict in the Kurdish border countries during the 2000s. The last area is the American Midwest. The chapters covering this region focus particularly on Norwegian immigrant communities in the United States, with detours to other parts of the world such as China and Troms in Norway. In all these time periods and geographical regions, the different encounters, contact and negotiations that took place between various actors and groups in both actual and metaphorical border areas are examined. This anthology originated with a research group in the Department of History at Volda University College and is also a tribute in honor of department’s 50th anniversary. It is mainly aimed at researchers and students in history, but may also be of interest to those working related fields such as religion, sociology or legal history, or general readers interested in history and culture. Tema for denne antologien er grenseområder og kontaktsoner, både som konkrete steder og som analytiske begreper for å forstå fortiden. Hva skjer når ulike kulturer, stater og mennesker møtes, og hva skjer i og med stedene og rommene der disse møtene skjer? Dette er blant spørsmålene som blir belyst i ni historiske undersøkelser som tar for seg flere forskjellige eksempler fra historien, fra det helt konkrete til det mer metaforiske, og fra stor skala til nærstudier. I tid spenner de ni bidragene fra overgangen fra middelalderen til tidlig nytid på begynnelsen av 1500-tallet helt frem til vår tid. Geografisk er undersøkelsene konsentrert om tre områder. Det ene er Norden. Her undersøkes både geografiske og kulturelle kontaktsoner både innad i og mellom ulike nordiske land. Flere av bidragene tar for seg perioden da Norge var del av en større nordeuropeisk konglomeratstat, Danmark-Norge. Det andre området er Midtøsten. Her omtales både hoffet som kontaktsone i Det osmanske riket og kontakt og konflikt i de kurdiske grenselandene på 2000-tallet. Det siste området er Midtvesten. Disse kapitlene har et særlig søkelys på det norske utvandrersamfunnet i Nord-Amerika, med avstikkere til andre deler av verden som Kina og indre Troms i Norge. I alle disse periodene og områdene undersøkes møter, kontakter og forhandlinger mellom aktører og grupper som foregikk i konkrete og metaforiske grenseområder, hvor det var ulike former for kontakt mellom aktører. Denne antologien springer ut fra forskningsmiljøet ved Historisk institutt ved Høgskulen i Volda og er også en markering av dette instituttets 50-årsjubileum. Den retter seg hovedsakelig mot forskere og studenter innen historie, men kan også være av interesse for nærliggende fagfelt som religion, sosiologi eller rettshistorie, eller andre lesere som er allment interessert i historie og kulturmøter.